Spectral, Thermal and Biological Studies of Mn(II) and Fe(II) Complexes of Schiff Base derived from fat p-Dimethylaminobenzaldehydeand Anthranilic Acid - Mehta, B.H.; Salunke, A.S. (Asian Journal of Chemistry, 2010)
The solid complexes of Mn(II) and Fe(II) with tridentate Schiff base, p-dimethylaminobenzylidene anthranilic acid (PDBAA) derived from p-dimethyl aminobenzaldehyde and anthranilic acid have been synthesized and characterized by elemental analysis, molar conductivity, IR, electronic spectra, magnetic susceptibility, X-ray diffraction studies and by thermal studies. From the analytical and spectral data, the stoichiometry of the complexes has been found to be 1 : 1 (metal : ligand). The metal chelates have a general formula [M (PDBAA)×(H2O)3] (M = Mn(II) Fe(II)). Electronic absorption data suggest octahedral geometry for these metals chelates. IR spectral data suggest that the ligand (PDBAA) behaves as a monobasic tridentate ligand with N : N : O donor sequence towards metal ions. Magnetic susceptibility measurement indicates paramagnetic behaviour for both the complexes. From electronic spectral data, various ligand field parameters such as Dq, B´, β and LFSE have been calculated for both the complexes, which are in good agreement with that of proposed geometries of the complexes. X-ray diffraction powder pattern indicates that these chelates are crystalline and crystallize with monoclinic system. The antifungal and antibacterial activities of the ligand and the complexes have been screened against several fungi and bacteria.